If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 6b = 30 Solving 2a + 6b = 30 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6b' to each side of the equation. 2a + 6b + -6b = 30 + -6b Combine like terms: 6b + -6b = 0 2a + 0 = 30 + -6b 2a = 30 + -6b Divide each side by '2'. a = 15 + -3b Simplifying a = 15 + -3b
| 4x-4/2x-2 | | -2?7=-3+t+24 | | x+.105x=5907 | | 75X-100y=400 | | 3x-8(-3x+5x)=24 | | ((8x/x^3-x^6/x^3))^-4/5 | | 4cos^2x+3secx-3-4cosx=0 | | -3.33333333333b=5 | | -3.33333333333b= | | -3=2x-x+y | | 16n^3+64n^2-4n-16=0 | | 7x+0y=180 | | 4/7x63 | | 3/8y-7=-5/8y | | 2y+(-2y)= | | 18*2/5 | | 5(x+3)=9x-11 | | 32×1/4 | | 7/10(190) | | -4(-5+m)=-8 | | f(8)=-1 | | g(x)=0.5x+13 | | 4+tanx=4 | | .9y=1.2x+72 | | Y=4-3*4/3 | | 4-3*-4/3 | | 4(x-5)=-20+4x | | p(p-.105)=5907 | | ×/9-15=15 | | 7y-3=6y+3 | | 4(x+6)-8x=-8 | | -4(n-2)=32 |